2014
DOI: 10.4317/medoral.19429
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of an intra-oral electrostimulator for the relief of dry mouth in patients with chronic graft versus host disease: Case Series

Abstract: Objectives: Patients with chronic graft-versus-host disease (cGVHD) often suffer from dry mouth and oral mucosal lesions. The primary objective of this study was to investigate the safety of an intra-oral electrostimulator (GenNarino) in symptomatic cGVHD patients. The secondary objective was to study the impact on the salivary gland involvement of cGVHD patients. Study Design: This paper presents a case series. The study included patients treated for 4 weeks, randomly assigned to the active device and then cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…13 Segundo a conferência do NIH, é o sialogogo de escolha, junto com a pilocarpina. O uso de eletroestimulador 21 não está descrito nas revisões de literatura, tão pouco nos consensos, apesar de uma série de casos alcançarem resultados significativos. Houve poucos efeitos colaterais, sua ocorrência se deu por meio do manuseio incorreto, pelo contato direto do aparelho com a mucosa.…”
Section: Resultsunclassified
“…13 Segundo a conferência do NIH, é o sialogogo de escolha, junto com a pilocarpina. O uso de eletroestimulador 21 não está descrito nas revisões de literatura, tão pouco nos consensos, apesar de uma série de casos alcançarem resultados significativos. Houve poucos efeitos colaterais, sua ocorrência se deu por meio do manuseio incorreto, pelo contato direto do aparelho com a mucosa.…”
Section: Resultsunclassified
“…[10] A study was performed by Zadik et al . [20] on six patients with graft versus host disease and it was concluded that the device usage is purely safe.…”
Section: Discussionmentioning
confidence: 99%
“…Sialagogue therapy, commonly Pilocarpine, remains an option but patients need close observation for development of any potential pulmonary side-effects ( 35 , 176 ). One study tested a soft mouth guard with electrostimulation providing apparent relief of symptoms; however, large-scale studies are needed to evaluate the efficacy ( 177 ). In the case of mucoceles, the effect of topical corticosteroids is non-significant, surgical removal or corticosteroid injection might improve clinical status, but this is seldom needed due to spontaneous recovery ( 35 , 173 , 178 ).…”
Section: Oral Cgvhd Management and Treatment Optionsmentioning
confidence: 99%